CRIMINAL LIABILITY IN ACTS OF SEXUAL ABUSE COMMITTED BY CHILDREN - Apriani Pasaribu; Ismaidar , Ismaidar; Abdul Rahman Maulana Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Child molestation is a complex issue involving legal, psychological, and social aspects. The juvenile justice system in Indonesia aims not only to punish but also to educate and rehabilitate child perpetrators. Through normative juridical methods and case approaches, this journal concludes that criminal responsibility for child perpetrators of sexual abuse has its own specificities compared to adult perpetrators, as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This journal examines the form of criminal responsibility for children who commit acts of sexual abuse by emphasizing a restorative approach and protection of children's rights. Law enforcement must adhere to the principles of the best interests of the child, rehabilitation, and social reintegration. Indonesian law provides a clear framework through the Juvenile Criminal Justice System Act, which primarily aims to protect children's rights, provide education, and provide rehabilitation